KNOWLEDGE AND AWARENESS OF CORONAVIRUS DISEASE-19 PROTOCOLS AMONG ANESTHESIA TECHNOLOGISTS AND TRAINEES IN WEST INDIA - WALODE, SUJATA; MORJE, KARAN; AHMAD, MOHAMMAD AKHLAQUE; DEBNATH, MANNA; OJHA, SANTOSH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The main objective of the study is to assess the knowledge and awareness of all the anesthesia technologists and trainees regarding coronavirus disease (COVID-19) infection control protocols. The health and safety of anesthesia technologists are of great importance which can ultimately aid in minimizing the risk of infection among them and facilitate them to offer exceptional care to the patients. Methods: This cross-sectional online survey was conducted on COVID-19 protocols using an online questionnaire that assesses the basic knowledge and awareness about infection control protocols. A total of 231 participant’s responses were recorded using Google form and analyzed using the Statistical Package for the Social Sciences. Results: The present study showed that participant’s overall knowledge was good but they were not well trained on infection control protocol. Only 19.04% of participants were well trained about the protocol. The majority of the participants are well aware of the Personal Protective Equipment’s-related information. Conclusions: To deal with this current situation, educational intervention on infection control protocol is urgently required to train Anesthesia technologists and trainees to defend against coronavirus.